Reductive dechlorination of trichloroethylene by polyvinylpyrrolidone stabilized nanoscale zerovalent iron particles with Ni - Kumar, Macharla Arun; Bae, Sungjun; Han, Seunghee; Chang, Yoonseok; Lee, Woojin (Journal of Hazardous Materials, 2017)
Abstract We developed a novel stabilized nanoscale zerovalent iron (NZVI) particles with Ni using an electron conducting polymer, polyvinylpyrrolidone (PVP), to selectively dechlorinate trichloroethylene (TCE) to non-toxic intermediates. The size of the PVP stabilized NZVI-Ni ((PVP-NZVI-Ni), average diameter: ∼20nm) is smaller than that of bare NZVI (50–80nm) due to the prevention of agglomeration of the resultant iron particles by PVP. PVP-NZVI-Ni showed a complete removal of TCE in 1h with superior dechlorination kinetics (kobs=5.702h−1) and ethane selectivity (98%), while NZVI-Ni showed 5 times slower dechlorination kinetics (1.218h−1). Other PVP-NZVI-metals (i.e., Cu, Sn, Co, and Mn) also enhanced the TCE dechlorination, but they were much slower (kobs=0.024−0.411h−1) than that of PVP-NZVI-Ni. In column test, PVP-NZVI-Ni exhibited better mobility (95% of PVP-NZVI-Ni recovery in the eluent) than NZVI-Ni (1%). In addition, PVP-NZVI-Ni reductively transform TCE to ethane even under 10 cycles of repeated TCE dechlorination treatment.
Keywords: Reductive dechlorination; Nano zerovalent iron (nZVI); Polyvinylpyrrolidone; Trichloroethylene; Bimetallic nZVI-Ni